A microwave irradiation-persulfate-formate system for achieving the detoxification and alkali-activated composite geopolymerization of the chromate-contaminated soil - Tao Huang; Lulu Zhou; Zhenxing Cao; Shuwen Zhang; Longfei Liu (Ecotoxicology and Environmental Safety, 2021)
A microwave (MA) irradiation-persulfate-formate system was constructed to detoxify Cr contamination and solidify the geopolymerization of the alkali-activated composite material. Three series of experiments were correspondingly conducted to evaluate the treatment for the chromate-contaminated soil. The changes in the molar ratios of formate to persulfate and the mass rates of fortifier to soil led to a significantly greater reduction of CrVI in the detoxification experiments. The increase of blast furnace slag from 50% to 80% in the composite cementitious materials (CCM) intensified the immobilization efficiencies of chromate and the compressive strengths of geopolymer blocks. MA irradiation potentially enhanced the binding of Ca cations to the aluminosilicate compounds. The degree of reaction in the phenomenological kinetics model mathematically verified the geopolymerization process. Ettringite was formed within the structure of the geopolymer in the coupling system. Sulfate radicals released from persulfate not only contributed to the detoxification process but also strengthened the immobilization process.